PERBANDINGAN EFEKTIFITAS UPAYA PREVENTIF SECARA INDIVIDUAL MENGGUNAKAN SIKAT GIGI MANUAL, SIKAT GIGI ELEKTRIK SERTA SIKAT GIGI MANUAL DENGAN DENTAL FLOSS DALAM PENCEGAHAN AKUMULASI PLAK (Kajian pada siswa-siswi SMPN 5 Depok, Sleman) - , NURAINI EFFENDI, drg. Dibyo Pramono, SU, MD.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One way to maintain oral health is to maximize the prevention of oral diseases. Prevention efforts can be done individually by using the manual toothbrush, an electric toothbrush or dental floss. The purpose of this study was to compare the effectiveness of individual preventive using the manual toothbrush, an electric toothbrush and a manual toothbrush with dental floss in the prevention of dental plaque accumulation (study on students in SMPN 5 Depok, Yogyakarta). This study used a quasi-experimental research design with pre-test and post-test group design. The subjects of this study are 45 students aged 11-14 years were divided into 3 groups and that have the inclusion and exclusion criteria. Group I used a manual toothbrush, group II used an electric toothbrush, and group III used a manual toothbrush with dental floss for 7 days. Subject is taken by consecutive sampling type of random allocation sampling. Plaque scores measured used plaque index PHP-M (Patient Hygiene Performance - Modified). The data is analyzed by One-Way ANOVA with 95% significant level. The results of this study showed that the reduction of early plaque score to final plaque score. The results of One-Way ANOVA shows there is no significant difference among the three groups subject used a manual toothbrush, an electric toothbrush and a manual toothbrush with dental floss (F = 1,314